2015
DOI: 10.1159/000368879
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Vascular Endothelial Growth Factor Is Decreased in Necrotizing Enterocolitis

Abstract: Background: Decreased intestinal perfusion may contribute to the development of necrotizing enterocolitis (NEC). Vascular endothelial growth factor (VEGF) is an angiogenic protein necessary for the development and maintenance of capillary networks. Whether VEGF is dysregulated in NEC remains unknown. Objectives: The objective of this study was to determine whether intestinal VEGF expression is altered in a neonatal mouse model of NEC and in human NEC patients. Methods: We first assessed changes of intestinal V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
2
29
0
1
Order By: Relevance
“…Recently, we found that VEGF-A is decreased in the intestinal samples of human NEC (36). Furthermore, using a mouse NEC model, we show here that VEGF-A (36) and VEGFR2 proteins are decreased in the intestine in the early stages of NEC development, before evidence of tissue necrosis, compared with DF controls.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Recently, we found that VEGF-A is decreased in the intestinal samples of human NEC (36). Furthermore, using a mouse NEC model, we show here that VEGF-A (36) and VEGFR2 proteins are decreased in the intestine in the early stages of NEC development, before evidence of tissue necrosis, compared with DF controls.…”
Section: Discussionsupporting
confidence: 48%
“…We previously found that VEGF-A is localized mainly to a few single intestinal epithelial cells and to some cells of the lamina propria and myenteric plexus (36). In this study, we further characterize the cells producing VEGF-A in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It is suggested that VEGF-mediated alterations of the intestinal mucosal microvasculature play an important role in NEC pathogenesis (9,13,24,25). In fact, intestinal VEGF protein expression is reduced in human and experimental NEC (9,26). The VEGF gene is highly polymorphic, especially in the promoter, 5 ′untranslated and 3 ′ -untranslated regions (27).…”
Section: Discussionmentioning
confidence: 99%